Effect of fractal fins on the heat storage performance of three-casing phase change accumulator - Guangtong TANG; Xin LI; Jingzhi JIANG; Lujiang LI; Guowei SHAO; Hongtao LI; Siyuan CHENG (Journal of Hebei University of Science and Technology)
In order to solve the problems of low heat storage efficiency and uneven melting in the phase change material area of the traditional heat accumulator, the influence of the length and branch angle of the Y-shaped fin on the heat storage performance of the three-tube phase change accumulator was simulated and studied by using FLUENT software to simulate the effects of the length and branch angle of the three-tube phase change accumulator with eightlongitudinal fins as the basic structure, ensuring that the volume of the fins in the accumulator remains unchanged, and the longitudinal fins are fractal with the "Y" shape. The results show that the addition of fractal fins in the three-tube phase change accumulator increases the heat exchange area compared with the ordinary longitudinal straight fin structure, which is conducive to the development of natural convection and effectively shortens the time required for the complete melting of PCM. After comprehensive analysis, the root and branches of the Y-shaped fin accounts for 25% and 75% of the total length, respectively, and the branch angle is 60°, which is the best Y-shaped fin structure, the complete melting rate of PCM is significantly improved, and the overall heat storage performance is improved.Compared with the ordinary straight fin heat accumulator, the proposed Y-shaped fin has more uniform heating of the phase change material and faster heat storage rate. The numerical simulation results provide certain data basis for the structural optimization design of the phase change heat accumulator.